Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The degree of the secondary school teacher using the Madrasati platform in education in Al-Baha regionMr. Fahed Salem AlRobai, Prof. Muhammad Hassan Al Sofran2. The Effectiveness of the Electronic Collabortion Learning for Developing the Mathematical Proficiency among Pre-service Mathematics TeachersMrs. Shohwd Sharaf Gharsan Sallam, Prof. Radman Mohamed Saeed3. Extant virtual lab. technology is used in teaching chemistry course in secondary schools in inclusive learning environment from the teachers’ perspectivesTeacher \ Mona Mafarh D. Al-Harhty, Co-Prof. Hanan Abdul Rahman Al-Arini4. Emotional intelligence and its relationship to the performance level of early childhood teachers in Hafr Al-Batin region, Saudi ArabiaMrs. Nada Remthan Al-Mukhtari Al-Shammari5. Dimensions of academic procrastination and its relationship to perceived self-efficacy among first-year undergraduate students at King Saud UniversityCo-Prof. Elsayed R, Boriek6. The Motivational Design of Digital learning Platforms using the (ARCS) Model and its Effectiveness in developing the Reading Comprehension among Middle School StudentsMr. Adnan Hassen Alobaidi, Prof. Ashraf Ahmed Zeidan7. Locus of control and its relationship to prejudice attitudes among Tafila Technical University students’Mrs. Saida H. Al-Qaisi, Prof. Ahmed M. Thawabieh
Keywords: Journal of Educational and Psychological Sciences